FACTORS WERE CORRELATED WITH LOWER BACK PAIN IN THE KPUM URBAN TRANSPORTATION DRIVERS OF SRIGUNTING – AMPLAS ROUTEIN 2018 - Panjaitan, Dewi Sintia (Fakultas Kesehatan Masyarakat Universitas Prima Indonesia, 2019)
In Indonesia, it is estimated that the prevalence rate of the incidence of the lower back pain is from 7.6% until 37% per person per year and in the workers’ problems which begin from young adults until the peak of prevalence at the age of 25-65 years. KPUM urban transportation drivers of Sri Gunting-Amplas route, Medan, have the risk for lower back pain. The objective of the research was to find out some factors which were correlated with lower back pain in the urban transportation drivers of Sri Gunting-Amplas route in 2018. The research was conducted at the KPUM terminal of Sri Gunting-Amplas route, Medan, from December, 2017 until January, 2018. It used analytic survey method with cross sectional design. The population was 30 drivers, and all of them were used as the samples (total sampling). The data were gathered by distributing questionnaires, NBM sheets for measuring lower back pain, and REBA sheets for measuring work behavior. The gathered data were processed by using Fisher exact statistical test at α = 0.05. The result of the research showed that based on age p-value = 0.031< α (0.05), the length of service p-value = 0.019 < α (0.05), and work attitude p-value = 0.022 < α (0.05). The conclusion was that there was the correlation of age, length of service, and work attitude with lower back pain in KPUM urban transportation drivers of Sri Gunting-Amplas route, Medan, in 2018. It is recommended that people prevent from illness caused by work like NPB (lower back pain), and urban transportation drivers take a rest in order to decrease NPB and arrange their sitting position while they are driving.